Produtores rurais do alto sertão sergipano : financiamento e estiagem em foco - Oliveira, Débora Catherine Santos (2015)
Agribusiness is characterized as a monoculture, mechanized, with high-tech application in large-scale production in large extensions of land, for exportation. With the globalization of agricultural production systems, several studies show that family farming has also developed productive dynamics associated to agribusiness. In separate and complementary niches, the federal government has established public policies for credit as PRONAF, PRONAMP directed to Brazilian farmers. For the semi-arid, region with great potential for agricultural production, despite the drought, there are specific programs such as PROAGRO, "Seeds of Life". From the perspective of financing agreements of agricultural funding signed by farmers (commercial farmers) from Canindé and Glória, located in the High Wilderness Lands of Sergipe (HWLS), in the period from 2010 to 2014 and the state bank of Sergipe, this work aims to analyze the relationship between the risk of dry climates and the effectiveness of public credit policies for financing the agricultural funding for farmers from HWLS. Based on the Comparative Method, it was possible to identify similarities and disagreements, regularities, and to notice facts which were inherent to socioeconomic and environmental development between the cities of Canindé and Glória from HWLS. Based on achieved results, it is concluded that in the town of Canindé, farmers were classified as small ones, with agricultural funding in areas from 1 to 1.5 ha, on average, and the main produced products as seed corn, guava and pumpkin, without the record of crop insurance, since it is considered a region of irrigated perimeter. In Glória, producers are medium-sized and have funded the agricultural funding in areas over 5 hectares for the production of corn, with payment of crop insurance because of the prolonged drought. Even knowing that the drought is not a decisive factor in obtaining financing and agricultural production, it is also necessary to ensure the production conditions in the region. Therefore, it is essential the participations of the farmers (subsistence and commercial), state and market, including financial agents, in a cooperative manner, so that we can achieve the goals of sustainable development (ODS) set by the UN.